Surface State Induced Filterless SWIR Narrow-Band Si Photodetector - Wang, Li; Pan, Yan; Xing, Jia-Le; Mao, Jian-Bo; Ba, Yong-Jin; Cao, Lu; Wang, Mo-Lin; Wu, Chun-Yan; Zhang, Xiang; Luo, Lin-Bao (IEEE electron device letters, 2023)
In this letter, planar type self-powered short-wavelength infrared narrowband Si photodetector was realized based on a simple Schottky structure by increasing surface states and enlarging the distance between Schottky electrode and light irradiation region. With the assistance of pyramid microstructure, the distance needed for sub-100 nm narrowband detection effectively decreased from 1000 μ m to 200 μ m, which is vital to improving device sensitivity and reducing device size. The obtained photodetector exhibited a response peak at 1119 nm with full-width at half-maximum of 97 nm. At zero bias, a peak detectivity up to 2.25 × 10 11 Jones, linear dynamic range of 91 dB and fast response speed (Rise time of 88 μ s and fall time of 118 μ s) were achieved. The higher wavelength selectivity and sensitivity than its counterpart with flat surface should be ascribed to the large number of surface state and pronounced light confinement effect of pyramid microstructure. This work opens up a new avenue for achieving planar-type narrowband photodetector that can provide better integration capabilities for on-chip applications than vertical devices.